Financial Performance and Share Price: The Moderating Role of Exchange Rate - Meliza Meliza; Dewi Yuniar Magetana; Andini Ayuningtyas (SIMAK, 2024)
Fluctuations that occur in the financial performance of food and beverages companies may have an impact on their share price. Economic instability and the impact of Covid-19 can reduce the company's financial performance and stock performance. Therefore, this research aims to examine the effect of financial performance on stock prices in food and beverages companies from 2018 to 2022. Moreover, the novelty of this research is that it applies the exchange rate as a moderating variable. This research uses liquidity ratios, profitability, and activity ratios in measuring the company's financial performance. Multiple regression analysis using a random-effect model was applied to measure the influence of liquidity, profitability, and activity on stock prices as well as the role of the exchange rate as a moderating variable. The results of analysis revealed that liquidity, profitability, and activity ratio have positive and significant effects on share prices. In addition, the exchange rate can moderate the relationship between profitability and share price as well as the relationship between activity ratios and share price.